The impact of website quality on customer satisfaction and eWOM in online purchase intention: The moderating role of gender in risk-taking - Saleem, Uzman; yi, Su; Bilal, Muhammad; Topor, Dan Ioan; Căpuṣneanu, Sorinel (Frontiers in Psychology, 2022)
The purpose of this study is to examine the effect of website quality, satisfaction, eWOM on online purchase intention in e-commerce context.A personal and online survey with 789 online Chinese shoppers belonging to four cities namely, Harbin, Shenyang, Guangzhou, and Shenzhen was conducted. Random samples were used to gather data. Validity and reliability tests, confirmatory factor analyses, and structural equation modeling were used to analyze the results. The results confirmed that WQ plays a vital role in obtaining CS and positive eWOM towards OPI of Chinese consumers and in gender investigation of risk-taking the female customers are risk-averse than male customers. Obviously, specific cities do not represent exactly all consumers related to the OPI of Chinese consumers. The OPI can be investigated in other cities in terms of consumer behavior and gender difference as well as other significant constructs that can be adopted for future research. The results of this research would provide help to managers and marketers of e-retailing about strategic planning in accordance with consumers’ OPI. The robust understanding of WQ influence on CS, eWOM, and OPI, as well as gender difference in OPI. The WQ is the most important factor in online shopping for CS, eWOM, and OPI. Understanding that how these factors influence the consumers' OPI as well as gender difference in OPI, this paper provides insightful guidance about these factors for e-retailers to improve the business.